Peningkatan Kreativitas Guru Pendidikan Anak Usia Dini Melalui Pembiayaan Program Desa Maju Inhil Jaya (DMIJ) Plus Terintegrasi - Mardianah; Yusria; Rianti, Ida; Najamuddin (Jurnal Indragiri Penelitian Multidisiplin, 2025)
Creativity is one of the competencies that a teacher needs to have. This research aims at investigating how important a government program in Indragiri Hilir Regency in supporting the creativity of PAUD teachers through the Allocation of Village Funds (ADD) in the Integrated plus of DMIJ program. The method used is qualitative research through interviews, documentation and direct observation. Thus, the author can conclude that the existence of this program is very helpful in developing, especially the management of PAUD in Faturrahman PAUD Village and Al Walid PAUD Village. Tanah Merah, Kab. Indragiri Hilir and has synergy that improves access to services, teacher competency and increased community participation in the Village PAUD Development program. The use of PAUD pilot funds for the Integrated DMIJ Plus Program can be said to be successful in increasing access, quality and competency of Faturrahman PAUD and Al Walid PAUD teachers with several factors that encourage PAUD teacher creativity through village fund financing through the integrated DMIJ PLUS program, namely as follows: Funding support, mentoring, learning facilities and infrastructure.